RESPONS PERTUMBUHAN BIBIT KARET (Hevea Brassilliensis Muell.Arg .) ASAL OKULASI TERHADAP APLIKASI PUPUK NPK (20-6-6) BERBEDA KONSENTRASI - Nasamsir Nasamsir (Jurnal Ilmiah Universitas Batanghari Jambi, 2008)
An experiment  was conducted to study NPK (20-6-6) at different concentration in growth increasing the Hevea seedling in Pattimura street, Jambi, from April to July 2008. Hevea seedling (PB 260) was grown in polybag, then NPK fertilizer was sprayed on the leaf surface twice a month in different concentration, namely 0.2 %, 0.4 %, 0.6 %, 0.8 %, and control. The experiment was carried out in completely randomized design with 3 replication. Response variable was RGR, NAR, and LAR from 14 to 70 days after planting. The result of  the experiment indicated that NPK (20-6-6) fertilizer significantly affect the RGR,NAR, and LAR Hevea seedling. The giving of NPK (20-6-6) is 0.2 % and control showed the lowest RGR , NAR, and LAR. The spray on concentration 0.6 % showed the highest RGR, NAR, and LAR , it was extremely different on concentration 0.2 % and 0.4 % and concentration 0.8 % was not significant with the concentration 0.6 % Key words ; Hevea seedling, (PB 260) ,  NPK (20-6-6), RGR, NAR, LAR